Pricing the priceless : a health care conundrum - Newhouse, Joseph P. (Walras-Pareto lectures (Unnumbered), 2002)
"In Pricing the Priceless, Joseph Newhouse explains the different pricing systems and how they affect resource allocation and efficiency. All pricing arrangements, he explains, involve trade-offs. The advantages of more inclusive bases of payment, for example, may be offset by incentives for providers to select good risks or to stint on the delivery of services."--BOOK JACKET.
Keywords: Medical care : United States; Medical economics : United States; Health insurance : United States; Economics, Medical; Insurance, Health : economics; Fee-for-Service Plans; Costs and Cost Analysis; terveydenhuolto; kustannukset; hinnoittelu; terveystaloustiede; sosiaalivakuutus